2009
DOI: 10.1080/02652030802425326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion supplementation of a commercial soft drink on tooth enamel erosion

Abstract: Acidic soft drinks are potentially erosive for dental hard tissues. This in vitro study evaluated the effect of calcium, fluoride, iron and phosphate, supplemented alone or in combination to a commercial citric acid-based carbonated beverage on dental erosion. Ninety enamel samples (4 x 4 x 3 mm) were randomly allocated to nine groups (n = 10): G1-pure beverage (control); G2-with 1 mM Ca; G3-with 0.047 mM F; G4-with 1 mM Fe; G5-with 1 mM P; G6 - with 1 mM Ca and 0.047 mM F; G7-with 1 mM Ca and 1 mM P; G8-with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 28 publications
2
23
1
12
Order By: Relevance
“…These results indicated that the juice with a lower amount of calcium can be a viable alternative to reduce the harmful effects of the orange juice on the teeth, with minor changes in taste alterations. Calcium lactate pentahydrate was chosen due to the fact that it is food-approved, nontoxic and has a high solubility ( 1 k sp ) [Van der Höven, 1985], and previous investigations have already demonstrated its capacity to act as an antierosive agent [Beiraghi et al,1989;Magalhães et al, 2009]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that the juice with a lower amount of calcium can be a viable alternative to reduce the harmful effects of the orange juice on the teeth, with minor changes in taste alterations. Calcium lactate pentahydrate was chosen due to the fact that it is food-approved, nontoxic and has a high solubility ( 1 k sp ) [Van der Höven, 1985], and previous investigations have already demonstrated its capacity to act as an antierosive agent [Beiraghi et al,1989;Magalhães et al, 2009]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies have observed that the addition of low quantities of calcium ( ϳ 0.4 g/l) can reduce the erosive potential of a blackcurrant juice drink [Hughes et al, 1999a, b;West et al, 1999]. Calcium has shown to be effective even at concentrations as low as 0.04 g/l [Attin et al, 2003[Attin et al, , 2005Magalhães et al, 2009], although this is not a consensus [Magalhães et al, 2010].…”
mentioning
confidence: 99%
“…One hundred and eighteen studies were retrieved, but only full papers in English were taken into consideration. In 76 papers, in vitro experiments were performed by using artificial saliva formulations, in which the following formulas were used most often -artificial saliva according to: (1) Klimek et al [1982], which was the first artificial formula introduced for in vitro studies (differences in mucin content) -17 studies [Attin et al, 1998[Attin et al, , 2000Lennon et al, 2006;Wiegand et al, 2006Wiegand et al, , 2007Magalhaes et al, 2008a;Wiegand et al, 2008aWiegand et al, , 2009aSouza et al, 2010;Wegehaupt and Attin, 2010;Yu et al, 2010a;Levy et al, 2011;Rochel et al, 2011;Magalhaes et al, 2011;Comar et al, 2012;Magalhaes et al, 2012]; (2) Vieira et al [2005] -17 studies [Kato et al, 2007;Magalhaes et al, 2007;Francisconi et al, 2008;Magalhaes et al, 2008b;Kato et al, 2009;Magalhaes et al, 2009;Rios et al, 2009;Bueno et al, 2010;Kato et al, 2010;Magalhaes et al, 2010a, b;Moretto et al, 2010;Barbosa et al, 2011;De Carvalho Filho et al, 2011;Manarelli et al, 2011;Barbosa et al, 2012;Cruz et al, 2012]; (3) Amaechi et al [1998b] -13 studies [Amaechi et al, 1998a…”
mentioning
confidence: 99%
“…They revealed that the mixture of Ca alone or in combination with P and F was effective to reduce the dental loss by Sprite, but not by Coke. On the other hand, the admixture 1 mM Ca, 1mM Fe, 1 mM P and 0.047 mM F to a soft drink (sprite zero) was not effective to decrease the erosive potential 63 .…”
Section: Modification Of Acid Solutions and Beveragesmentioning
confidence: 90%
“…On the other hand, the admixture of low concentrations of Fe (1mM) into a soft drink (sprite zero) were not able to reduce the enamel loss 63 .…”
Section: Modification Of Acid Solutions and Beveragesmentioning
confidence: 92%